Effect of NaClO disinfection/cleaning on passive films on AISI 316L - Tranchida, G.; Di Franco, Francesco; Virtanen, Sannakaisa; Santamaria, M. (Corrosion Science, 2020)
316 L stainless steel samples were passivated in NaClO containing solutions in order to simulate disinfection processes. Passive films were grown at the open circuit potential by immersion in NaClO aqueous solutions at different concentrations and temperature in order to understand how exposure to aggressive environments could affect subsequent corrosion resistance of SSs. In the attempt to study the passive film growth mechanism, in-situ Open Circuit Potential measurements were performed in the same growth solutions. Photoelectrochemical and impedance investigation of passive films was carried out in order to link their solid state properties with their corrosion behaviour.
CRIS-Team Scopus Importer:2021-04-19
Keywords: EIS; Passivity; Polarization; Stainless steel; Transpassivity; XPS